Comparison of heavy metal phytoremediation in monoculture and intercropping systems of Phyllostachys praecox and Sedum plumbizincicola in polluted soil. Issue 5 (16th April 2018) - Bian, Fangyuan; Zhong, Zheke; Wu, Shengchun; Zhang, Xiaoping; Yang, Chuanbao; Xiong, Xiaoyi
ABSTRACT: A bamboo species ( Phyllostachys praecox ) and a Cd/Zn hyperaccumulator ( Sedum plumbizincicola ) were tested under different planting systems to compare their heavy metal phytoremediation ability. P. praecox (MP), S. plumbizincicola (MS) and P. praecox × S. plumbizincicola (IPS) plantations were established in Cu, Zn, and Cd-contaminated soil. Soil properties and heavy metal contents in plants were determined and compared after four years of plantation establishment. The rankings of available and total metal contents in soil layers were MP > MS > IPS (0–20 cm) and MP > IPS > MS (20–40 cm, except for Cu), respectively. The Cu and Zn contents in mature bamboo tissues were significantly lower, but the Cd contents in bamboo tissues (except for leaves) higher, in the IPS than in the MP. The bioconcentration and the translocation factors in most of bamboo tissues showed an increasing trend from the MP to the IPS. Heavy metal distribution in plants is greatly affected by the planting patterns. The tested intercropping system of two plant species showed higher biomass productivity, implying more heavy metals can be removed from the soil through the harvesting of plants. Therefore, the IPS leads to significant improvement of soil phytoremediation.